2019
DOI: 10.7759/cureus.6341
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Approach to Manage Gastrointestinal Bleeding with a Left Ventricular Assist Device (LVAD)

Abstract: Left ventricular assist devices (LVADs) are an exceedingly important form of mechanical support for patients with end-stage heart failure. LVADs can be utilized both as a bridge to cardiac transplant and also as a definitive treatment. However, a few complications are associated with LVAD placement, the most common and cumbersome of which is gastrointestinal (GI) bleeding with an incidence of about 30%. These bleeding events often require transfusion therapy, but they are rarely fatal. The etiologies of GI ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…This large observational study analyzes GIB in continuous-flow LVAD patients, investigating clinical patterns that can inform the clinical evaluation and management of these complex patients. Our findings confirm a high rate of GIB, especially in destination patients, and show a low diagnostic yield for colonoscopy and middle GI bleed assessments in LVAD patients who present with occult bleeding ( 15 18 ). Overt bleeding was more frequent and may originate from anywhere in the GI tract.…”
Section: Discussionsupporting
confidence: 74%
“…This large observational study analyzes GIB in continuous-flow LVAD patients, investigating clinical patterns that can inform the clinical evaluation and management of these complex patients. Our findings confirm a high rate of GIB, especially in destination patients, and show a low diagnostic yield for colonoscopy and middle GI bleed assessments in LVAD patients who present with occult bleeding ( 15 18 ). Overt bleeding was more frequent and may originate from anywhere in the GI tract.…”
Section: Discussionsupporting
confidence: 74%
“…Further longitudinal studies possibly using artificial intelligence algorithms are needed for better risk stratification. This review summarizes the most recent literature and differs from existing reviews and systematic reviews in that it is focused on the overall management with a suggested algorithm which includes pump speed adjustments 81,82 …”
Section: Discussionmentioning
confidence: 99%
“…This review summarizes the most recent literature and differs from existing reviews and systematic reviews in that it is focused on the overall management with a suggested algorithm which includes pump speed adjustments. 81,82 To date, a definitive strategy to manage GIB has not been identified, medical therapy targeting different pathophysiologic mechanisms of these lesions has been evaluated as primary and secondary preventative therapy for GIB in LVAD patients and needs further investigation. Based on the present literature review, we propose an algorithm for management of GIB in the acute and chronic settings.…”
Section: Discussionmentioning
confidence: 99%
“…In cases where the source of bleeding cannot be identified, the following measures have been reported to be used; capsule endoscopy, balloon enter-oscopy, tagged red cell scan and angiogram (mesenteric). Besides the preliminary management techniques outlined earlier, other therapeutic options employed in the management of GIB in these patients include electrocoagulation, laser photocoagulation, injection of hemostatic solutions, endoscopic ligation, use of argon plasma, clipping, and transcatheter embolization [53][54][55]. In severe cases with poor hemodynamics, surgical approach may be utilized as a diagnostic and therapeutic measure.…”
Section: Discussionmentioning
confidence: 99%
“…The use of direct thrombin and factor Xa inhibitors was not mentioned in any of the studies. Adequate blood pressure control and post-operative monitoring is advised to attain better outcomes [47][48][49][50][51][52][53][54][55]. Few studies have explored the use of genotype-guided warfarin therapy in these patients with most reporting promising outcomes with its use [56][57][58].…”
Section: Discussionmentioning
confidence: 99%